Influence of acceleration of the fist on the effectiveness of the straight punch in taekwondo - Wasik, J.; Borysiuk, Z.; Balko, S. (Archives of Budo Science of Martial Arts and Extreme Sports, 2017)
Background & Study Aim: In its traditional version the taekwon-do straight punch is an important element in the coaching of martial arts practitioners. In sports competition, these strikes are used most often when attacking or counter-attacking, and also in power tests, they are a considerably significant technique when it comes to granting a victory. This is the reason why this study has focused on the relationships between acceleration and other kinematic factors involved in the execution of the straight punch (in taekwondo referred to as ap jumok jirugi) and whether from the point of view of biomechanics there are differences between the dominant and non-dominant hand.